اللہ تعالیٰ کی صفت رحمت کے انسانی زندگی پر اثرات: Impact of Allah Almighty’s attribute of Kindness on Human life (Al-Qamar, 2020)
The attribute of mercy of Allah almighty prevails over all other attributes. No matter how severely Allah Almighty treats man, in terms of purpose, the good of man lies in it. In this sense, the aspect of mercy is also found in all the other attributes. The attribute of mercy has a positive and profound effect on the human personality and character. As a result, a feeling of pity and compassion for other creatures is created in man. Moreover, it draws man’s attention to the performance of good deeds. Above all, those who go to extremes in committing major sins are saved from falling into the mire of error, disorder and rebellion when the good news of forgiveness is announced as a result of repentance.
Keywords: Attribute of mercy; Human character and morality; safety from sin and ignorance